Psikolinguistik sebagai Pendekatan Komunikasi Dakwah pada Generasi Milenial - Bachtiar, M. Anis; Prihananto; Arifin, Bustanul; Retpitasari, Ellyda (Jurnal Ilmu Komunikasi, 2022)
The purpose of this research is to reveal the forms of communication approaches in preaching by Ustad Iwan Zuswantoro at Padepokan Kandang Badak and the results of his preaching communication approach towards the congregation. The researcher employed a qualitative research method with the phenomenological approach of Edmund Husserl. The findings indicate that there are three preaching communication approaches, namely psycholinguistic approaches: 1) Language, utilizing precise language selection (diction) to facilitate the congregation's understanding of the material. 2) Utilizing intonation and articulation, accompanied by nonverbal language support such as facial expressions and gestures, creating a comfortable atmosphere for the members during the lectures at the padepokan. 3) Providing content that matches the capacity of the members and focusing on problem-solving in the teaching material, motivating the congregation to practice according to their individual abilities. Tujuan penelitian ini mengungkapkan bentuk pendekatan komunikasi dakwah ustad Iwan Zuswantoro di Padepokan Kandang Badak dan hasil pendekatan komunikasi dakwah ustad Iwan Zuswantoro di Padepokan Kandang Badak tarhadap jamaahnya. Peneliti menggunakan metode penelitian kualitatif dengan pendekatan fenomenologi Edmund Husserl. Hasil penelitian menunjukkan bahwa ada 3 (tiga) pendekatan komunikasi dakwah sebagai pendekatan psikolinguistk, yaitu; 1). Bahasa, yang digunakan menggunakan pemilihan bahasa (diksi) yang tepat, sehingga jamaah merasa mudah memahami materi pengajian. 2). Menggunakan intonasi dan artikulasi serta disertai dengan dukungan bahasa nonverbal yaitu mimik dan gesture, anggota merasa nyaman mengikuti pengajian di padepokan. 3). Materi yang sesuai dengan kapasitas anggota dan materi pengajian yang berorentasi pada problem solving, jamaah termotivasi untuk mengamalkan sesuai dengan kecakapan masing-masing.